Quantitative allele-specific expression and DNA methylation analysis of H19, IGF2 and IGF2R in the human placenta across gestation reveals H19 imprinting plasticity. - Sam Buckberry (Public Library of Science (PLoS), 2012)
Imprinted genes play important roles in placental differentiation, growth and function, with profound effects on fetal development. In humans, H19 and IGF2 are imprinted, but imprinting of IGF2R remains controversial. The H19 non-coding RNA is a negative regulator of placental growth and altered placental imprinting of H19-IGF2 has been associated with pregnancy complications such as preeclampsia, which have been attributed to abnormal first trimester placentation. This suggests that changes in imprinting during the first trimester may precede aberrant placental morphogenesis. To better understand imprinting in the human placenta during early gestation, we quantified allele-specific expression for H19, IGF2 and IGF2R in first trimester (6-12 weeks gestation) and term placentae (37-42 weeks gestation) using pyrosequencing. Expression of IGF2R was biallelic, with a mean expression ratio of 49:51 (SD = 0.07), making transient imprinting unlikely. Expression from the repressed H19 alleles ranged from 1-25% and was higher (P<0.001) in first trimester (13.5 ± 8.2%) compared to term (3.4 ± 2.1%) placentae. Surprisingly, despite the known co-regulation of H19 and IGF2, little variation in expression of the repressed IGF2 alleles was observed (2.7 ± 2.0%). To identify regulatory regions that may be responsible for variation in H19 allelic expression, we quantified DNA methylation in the H19-IGF2 imprinting control region and H19 transcription start site (TSS). Unexpectedly, we found positive correlations (P<0.01) between DNA methylation levels and expression of the repressed H19 allele at 5 CpG's 2000 bp upstream of the H19 TSS. Additionally, DNA methylation was significantly higher (P<0.05) in first trimester compared with term placentae at 5 CpG's 39-523 bp upstream of the TSS, but was not correlated with H19 repressed allele expression. Our data suggest that variation in H19 imprinting may contribute to early programming of placental phenotype and illustrate the need for quantitative and robust methodologies to further elucidate the role of imprinted genes in normal and pathological placental development.